Spectrophotometric Determination of Cobalt(II) with Phenanthrenequinonemonosemicarbazone - Rai, H.C.; Ranjan Kumar, Shiv; Singh, K.B. (Asian Journal of Chemistry, 2010)
When phenanthrenequinonemonosemicarbazone reacts with cobalt(II), a red precipitate is formed on heating. The precipitate is partially soluble in ethanol and chloroform and soluble in dimethylformamide. Because of the intensity and stability of the colour formed with cabalt(II) this system has been studied in detail with a view to utilise this reaction for the spectrophotometric determination of the metal.